COMBINING ABILITY ANALYSIS FOR SEED YIELD AND ITS YSIS FOR SEED YIELD AND ITS CONTRIBUTING TRAITS IN LINSEED ( CONTRIBUTING TRAITS IN LINSEED (Linum usitatissimum L.) - K. P. S. TOMAR, AJEET KUMAR ,; A. KUMAR; N. K. VASISTHA, V. RATHI , (The Bioscan, 2018)
A field experiment was conducted at Crop Research Centre (Chirodi), Sardar Vallabhbhai Patel University of Agriculture & Technology, Meerut (U.P.), during Rabi 2012-13 and 2013-14 to estimate combining ability (GCA and SCA) of seed yield and its components of linseed. The experimental material comprised of ten parents and their 45s F2. The hybrids F2 were evaluated along with their parents in randomized complete block design with three replications. It revealed highly significant variances for GCA and SCA for all the characters. Combining ability studies revealed that the lines Shekhar, Kiran, T-397 and Mukta, which were showed high general combining ability effects in desirable direction for seed yield and yield components. Moreover,. Among the specific cross combinations, the crosses for seed yield per plant viz., Kiran×T-397, Shubhra×Hira, Neelam×Hira, T-397×Neelam and T-397×Hira exhibited good specific combining ability effects for seed yield and its contributing traits.